Impact of Sufficiency Economy Philosophy on Textile Business of Thai-Chinese Entrepreneurs : A Case Study Bobae Market: ผลกระทบของปรัชญาเศรษฐกิจพอเพียงที่มีต่อธุรกิจสิ่งทอของผู้ประกอบการคนไทยเชื้อสายจีน กรณีศึกษา ตลาดโบ๊เบ๊ - kanyapakkajon, sawaros (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
The main objective of this research is to study the effect of the Sufficiency Economy Philosophy on the textile business of the Chinese people in the Bobae market. The research consisted of 345 questionnaires and interviews with 10 related persons using descriptive statistics, percentage, mean and standard deviation. The research found Sufficiency Economy Philosophy has a quantifiable impact. that Applying Sufficiency Economy Philosophy has the effect of making business prosper, understanding the present situation with moderation. To be able to stay steady with access to theoretical and applied theories using rationality .Sustainable development can be done in the future with the principle of immunity. Examples of such effects. Material Handling from Upstream to Downstream Design their own products Domestic and foreign markets. Maintain the standard of Thai textiles. They are shared with the community. Quantitative Impact on Thai-Chinese Businesses Relieved from Economic Crisis Have a better life Be ready to change in the context. They have the ability to encourage their children to receive good education, knowledge and virtue in the management of family affairs cause. Know how to solve And can prevent future risks. The results showed that the mean was 3.89 and the standard deviation was .569. Qualitative impact makes a business an asset. The performance of the Company is significantly higher.